An Approach to Implement Cost Efficient Space Detection Technology with Lower Complexity for Smart Parking System - Himal Pratap Singh; Om Prakash Uniyal; Kireet Joshi (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
As the population of world is growing day by day, there is a rapid increment in the vehicle production. With the increase in number of the vehicles, more parking spaces and efficient ways of parking are required. In the proposed system, a new and cost efficient way of finding the free spaces in parking lot is proposed and also different space detection technologies are compared. This system will be helpful for the drivers in finding the vacant spaces in the car parking lots using a simple technology in which a balloon will be used to determine the vacant parking spaces. Since this technology is cost efficient and effective,this system is termed as smart parking system.